2015
DOI: 10.1038/nature14272
|View full text |Cite
|
Sign up to set email alerts
|

Vapour-mediated sensing and motility in two-component droplets

Abstract: Controlling the wetting behaviour of liquids on surfaces is important for a variety of industrial applications such as water-repellent coatings and lubrication. Liquid behaviour on a surface can range from complete spreading, as in the 'tears of wine' effect, to minimal wetting as observed on a superhydrophobic lotus leaf. Controlling droplet movement is important in microfluidic liquid handling, on self-cleaning surfaces and in heat transfer. Droplet motion can be achieved by gradients of surface energy. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

16
410
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 389 publications
(431 citation statements)
references
References 31 publications
16
410
5
Order By: Relevance
“…Accordingly, they always approach each other. This explains the experimentally observed motions of pair W or PG droplets [7] which have not been explained so far.…”
supporting
confidence: 65%
See 3 more Smart Citations
“…Accordingly, they always approach each other. This explains the experimentally observed motions of pair W or PG droplets [7] which have not been explained so far.…”
supporting
confidence: 65%
“…Equally complex motion of droplets (attraction, repulsion, chasing etc) has been reported for volatile droplets slowly evaporating at room temperature [2][3][4][5][6][7], but, apart from the conjecture that the phenomena is caused by the Marangoni effect (flow induced by the gradient of surface tension), no quantitative theory has been given. Cira et al [7] reported that evaporating droplets show complex motion even if they are placed on an inert substrate where the wettability is uniform and unchanged. Figure 1 schematically shows their results for the case of pure liquid droplets.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the large majority of cases, the drop motion is induced by an interfacial energy gradient at a solid/liquid interface (wettability gradient) and/or at a free interface (Marangoni stress) 3. This has resulted in a plethora of studies to elucidate the fundamental mechanisms that convert such gradients into drop motion4 as well as to develop strategies to manipulate drops under the control of various external signals, such as thermal,5 electrical2, 6, 7 and optical8, 9, 10, 11, 12, 13 stimuli. Most of these approaches necessitate the implementation of rather complex components, such as electrodes or optical elements, or the development of systems that are intrinsically responsive to the desired stimulus, such as photo‐ or thermosensitive substrates 8, 9.…”
mentioning
confidence: 99%